Forest Age Rivals Climate to Explain Reproductive Allocation Patterns in Forest Ecosystems Globally - Rachel E. Ward; Huanyuan Zhang‐Zheng; Kate Abernethy; Stephen Adu‐Bredu; Luzmilla Arroyo; Andrew Bailey; Jos Barlow; Erika Berenguer; Liana Chesini‐Rossi; Percival Cho; Cecilia A. L. Dahlsjö; Eder Carvalho das Neves; et al. (Ecology Letters, 2025)
Forest allocation of net primary productivity (NPP) to reproduction (carbon required for flowers, fruits, and seeds) is poorly quantified globally, despite its critical role in forest regeneration and a well‐supported trade‐off with allocation to growth. Here, we present the first global synthesis of a biometric proxy for forest reproductive allocation (RA) across environmental and stand age gradients from a compiled dataset of 824 observations across 393 sites. We find that ecosystem‐scale RA increases ~60% from boreal to tropical forests. Climate shows important non‐linear relationships with RA, but is not the sole predictor. Forest age effects are comparable to climate in magnitude (MAT: ß = 0.24, p = 0.021; old growth forest: ß = 0.22, p p = 0.001; soil N: ß = −0.07, p = 0.001). These results provide strong evidence that ecosystem‐scale RA is mediated by climate, forest age, and soil conditions, and is not a globally fixed fraction of positive NPP as assumed by most vegetation and ecosystem models. Our dataset and findings can be used by modellers to improve predictions of forest regeneration and carbon cycling.

Role of Prices and Wealth in Consumer Demand for Bushmeat in Gabon, Central Africa - DAVID S. WILKIE; MALCOLM STARKEY; KATE ABERNETHY; ERNESTINE NSTAME EFFA; PAUL TELFER; RICARDO GODOY (Conservation Biology, 2005)
Unsustainable hunting of wildlife for food is often a more immediate and significant threat to the conservation of biological diversity in tropical forests than deforestation. Why people eat wildlife is debated. Some may eat bushmeat because they can afford it; others may eat it because it is familiar, traditional, confers prestige, tastes good, or adds variety. We completed a survey of 1208 rural and urban households in Gabon, Africa, in 2002–2003 to estimate the effect of wealth and prices on the consumption of wildlife and other sources of animal protein. Consumption of bushmeat, fish, chicken, and livestock increased with increasing household wealth, and as the price of these commodities rose, consumption declined. Although the prices of substitutes for bushmeat did not significantly, in statistical terms, influence bushmeat consumption, as the price of wildlife increased and its consumption fell, the consumption of fish rose, indicating that fish and bushmeat were dietary substitutes. Our results suggest that policy makers can use economic levers such as taxation or supply reduction through better law enforcement to change demand for wildlife. These measures will help to regulate unsustainable exploitation and reduce the risk of irreversible loss of large‐bodied and slow‐reproducing wildlife species. If policy makers focus solely on reducing the unsustainable consumption of wildlife, they may see adverse impacts on the exploitation of fish. Furthermore, policy makers must ensure that raising household wealth through development assistance does not result in undesirable impacts on the conservation status of wildlife and fish.

Mitochondrial DNA phylogeography of western lowland gorillas ( Gorilla gorilla gorilla ) - Stephen L. Clifford; Nicola M. Anthony; Mireille Bawe‐Johnson; Kate A. Abernethy; Caroline E. G. Tutin; Lee J. T. White; Magdelena Bermejo; Michelle L. Goldsmith; Kelley McFarland; Kathryn J. Jeffery; Michael W. Bruford; E. Jean Wickings (Molecular Ecology, 2004)
The geographical distribution of genetic variation within western lowland gorillas ( Gorilla gorilla gorilla ) was examined to clarify the population genetic structure and recent evolutionary history of this group. DNA was amplified from shed hair collected from sites across the range of the three traditionally recognized gorilla subspecies: western lowland ( G. g. gorilla ), eastern lowland ( G. g. graueri ) and mountain ( G. g. beringei ) gorillas. Nucleotide sequence variation was examined in the first hypervariable domain of the mitochondrial control region and was much higher in western lowland gorillas than in either of the other two subspecies. In addition to recapitulating the major evolutionary split between eastern and western lowland gorillas, phylogenetic analysis indicates a phylogeographical division within western lowland gorillas, one haplogroup comprising gorilla populations from eastern Nigeria through to southeast Cameroon and a second comprising all other western lowland gorillas. Within this second haplogroup, haplotypes appear to be partitioned geographically into three subgroups: (i) Equatorial Guinea, (ii) Central African Republic, and (iii) Gabon and adjacent Congo. There is also evidence of limited haplotype admixture in northeastern Gabon and southeast Cameroon. The phylogeographical patterns are broadly consistent with those predicted by current Pleistocene refuge hypotheses for the region and suggest that historical events have played an important role in shaping the population structure of this subspecies.